2016
DOI: 10.7896/j.1630
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond FADN: The use of additional data to gain insights into extension service use across European Union Member States

Abstract: This paper examines the use of extension services by farm households across eight European Union (EU) Member States, exploring the type of extension service engaged with, the degree of engagement and the type of information sought. The impact of extension on economic, environmental and social sustainability is also considered. European data utilised are those collected from a pilot sample of 820 households in 2015/2016 as part of the EU Framework 7 project FLINT, from which the Irish results are incorporated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Furthermore, frequency of PM use can also be interpreted as an indicator of the level of engagement with advisory services. In this context, the findings confirm that higher levels of engagement with agricultural extension services are positively associated with greater technical and financial change as observed in previous studies (Läpple et al, 2013;Brennan et al, 2016;Nordin and Höjgård, 2017). Finally, frequent PM users had greater SFP per hectare than nonusers (Table 3), which indicated that this category has a history of intensive farming and greater scale as such payments were established almost a decade before the current study period commenced.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, frequency of PM use can also be interpreted as an indicator of the level of engagement with advisory services. In this context, the findings confirm that higher levels of engagement with agricultural extension services are positively associated with greater technical and financial change as observed in previous studies (Läpple et al, 2013;Brennan et al, 2016;Nordin and Höjgård, 2017). Finally, frequent PM users had greater SFP per hectare than nonusers (Table 3), which indicated that this category has a history of intensive farming and greater scale as such payments were established almost a decade before the current study period commenced.…”
Section: Discussionsupporting
confidence: 88%
“…Further, Martino et al [21] assessed the efficiency and sustainability of fertilization programs for wheat production in the Umbria region (Central Italy). Brenann et al [22] demonstrated that measuring sustainability allowed for comparisons between farmers who use extension services and those who do not among eight EU countries. Basing their paper on the FADN network, Koloszko-Chomentowska and Zukovskis [23] explored the sustainability of organic farming versus conventional farming in Poland.…”
Section: Review Of the Farm Sustainability Assessment Based On Fadn Datamentioning
confidence: 99%
“…Such hybrid databases have been especially used for evaluation and controlling in rural and agricultural development, (Brennan et al. 2016 ; Bozzo et al. 2019 ; OECD 2019 ; Finger and El-Benni 2021 ; Michalek 2022 ).…”
Section: Data Types Generation Of Small-scale Spatial Data and The Ra...mentioning
confidence: 99%